Relationship Between Level of Maternal Knowledge about Nutrition of Pregnant Women with the Incidence of Stunting in Children Under Five - Erik Johan; Achmad Dafir Firdaus; Reny Tri Febriani; Regista Trigantara (Malahayati Nursing Journal, 2024)
ABSTRACT Stunting can be caused by several factors, including poor nutritional intake during pregnancy in toddlers. Some of them are readiness to become mothers where this is motivated by a very high rate of early marriage. Unpreparedness in facing motherhood can affect perceptions in parenting. This study aims to determine the relationship between the level of maternal knowledge about nutrition of pregnant women with the incidence of stunting in children under five in Sisir Village, Batu City with a cross-sectional analytical descriptive design involving 56 respondents consisting of maternal respondents and toddlers aged 1-5 years with purposive sampling techniques.  Data were collected with maternal knowledge level questionnaires during pregnancy and z score graphs. Results: Data analysis using Spearman Rank test with α = 0.05. The results showed that the significance value (sig) or p value was 0.009. Because the value of sig (0.009) (0.05) with a correlation value of 0.347, the results of the data obtained from respondents mean h0 rejected h1 accepted. There is a relationship between the level of knowledge of parents and the incidence of stunting in toddlers.  The results of the study concluded that there is a significant relationship between the level of knowledge of parents and the incidence of stunting in toddlers. Discussion: In Batu city comb sub-district. It is hoped that mothers can try to find knowledge and information related to nutrition and other factors that can cause stunting, and mothers can start paying attention to nutrition during pregnancy for preventive measures against the impact of stunting on the development of the next child at birth. Keywords: Maternal Knowledge, Gestation Period, Incidence Of Stunting